Variability of Ionosphere Over Indian Longitudes to a Variety of Space Weather Events During December 2006 - Alok Kuman Ranjan; M. V. Sunil Krishna; C. Amory‐Mazaudier; R. Fleury; S. Sripathi; Geeta Vichare; W. Younas (Space Weather)
Abstract This paper highlights the impact of intense solar events over India during 3–20 December 2006. Ionospheric effects of a major solar flare (X9) on December 5 (10:35 UT) have been investigated by using dayside and nightside magnetometer data, dayside ionosondes, and dayside GPS vTEC observations. On the next day, a stream of fast solar wind hits the magnetosphere, causing a HILDCAA (High Intensity Long Duration Continuous Auroral Activity) preceded by moderate geomagnetic storm. The origin and characteristics of a positive ionospheric storm which occurred over Tirunelveli (TIR, geomagnetic latitude: −0.18°N) in the recovery phase of storm due to simultaneous presence of enhanced O/N2 and WEJ or weakened EEJ during the HILDCAA (7th and 8th of December) is investigated. Subsequently, on December 14, the most powerful CME since the Halloween event impacts the Earth, and three SSCs are recorded on December 14, 16, and 18. The variability of the ionosphere over the Indian longitude sector due to these intense space weather fluctuations is presented by utilizing the magnetometers, ionosonde, GPS vTEC, and satellite‐based observations in the same region. This study reports the influence of prompt penetration of the magnetospheric convection electric field and the disturbance dynamo on several key ionospheric and magnetic parameters within the Indian longitude sector.